2013
DOI: 10.1021/bi400316p
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the Substrate Specificity of CMP N-Glycosidase to dCMP

Abstract: MilB is a CMP hydrolase involved in the early steps of biosynthesis of the antifungal compound mildiomycin. An enzyme from the bacimethrin biosynthetic pathway, BcmB, is closely related in both sequence and function to MilB. These two enzymes belong to the nucleoside 2′-deoxyribosyltransferase (NDT) superfamily. NDTs catalyze N-glycosidic bond cleavage of 2′-deoxynucleosides via a covalent 2-deoxyribosyl-enzyme intermediate. Conservation of key active site residues suggests that members of the NDT superfamily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 37 publications
(122 reference statements)
3
25
0
Order By: Relevance
“…As the k cat of MilB for hmCMP in reference (8) is 3.1×10 −3 s −1 , even lower than that for MilB for CMP reported by Megan D. Sikowitz et al. (9), the kinetic data obtained by this study, therefore, look more consistent and convincing (Table 1). These variations might arise by the way for calculating the peak area of the products, type of column and separation conditions used for HPLC as well as protein activity and purity in different preparations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As the k cat of MilB for hmCMP in reference (8) is 3.1×10 −3 s −1 , even lower than that for MilB for CMP reported by Megan D. Sikowitz et al. (9), the kinetic data obtained by this study, therefore, look more consistent and convincing (Table 1). These variations might arise by the way for calculating the peak area of the products, type of column and separation conditions used for HPLC as well as protein activity and purity in different preparations.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, the Steven E. Ealick group reported the crystal structure of MilB in complex with CMP and revealed that the F17Y mutation of MilB completely reversed its substrate specificity from CMP to dCMP (9). However, CMP is not the natural and the most preferred substrate for MilB.…”
Section: Introductionmentioning
confidence: 99%
“…The SARM1-TIR domain was modeled using the crystal structure of two enzymes identified from our prediction: MilB Cytidine 5’ monophosphate (CMP) Hydrolase (PDB: 4JEM) (Figure 4B) and Nucleoside 2-deoxyribosyltransferase (PDB: 1F8Y) (Figure S4B). Importantly, we found that a glutamic acid E642 in the SARM1-TIR domain aligned with both the key catalytic glutamic acid residue in CMP hydrolase (Sikowitz et al, 2013) and the proposed nucleophilic glutamic acid in the active site of nucleoside 2-deoxyribosyltransferase (Armstrong et al, 1995) (Figure 4A, 4B and S4C). Moreover, glutamic acid residues are also known catalytic residues in other NADases (Ghosh et al, 2010).…”
Section: Resultsmentioning
confidence: 91%
“…However, in addition to these TIR domains, we also detected a number of nucleotide hydrolase/transferase enzymes (Table S2). For some of these enzymes, residues that contribute to catalytic activity have been established (Sikowitz et al, 2013; Armstrong et al, 1995). We therefore used structural modeling and sequence alignments to identify putative residues in the SARM1-TIR domain that might contribute to enzymatic activity (Figure 4A, 4B, S4A, S4B).…”
Section: Resultsmentioning
confidence: 99%
“…Point mutations predicted to inactivate the catalytic site of the RT (D216A/D217A in the RT of Ec48, and D189A/D190A in the RT of Ec73) completely abolished defense, indicating that reverse transcription of the retron is essential for defense. In addition, an E117Q point mutation predicted to inactivate the catalytic site of the ribosyltransferase domain of the Ec73 effector 26 , led to a non-functional system, and similarly, deletion of the transmembrane helices of the gene associated with the Ec48 retron also abolished defense (Figure 3, Supplementary Figure 3). Together, these results show that retrons, functioning together with their associated effector genes, form anti-phage defense systems.…”
Section: Figure 1 a Retron-containing Genetic System Protects Againsmentioning
confidence: 99%